Psikoedukasi mengenai stunting pada anak dan peran pengasuhan orangtua untuk meningkatkan pengetahuan mengenai stunting - Dwi Nur Rachmah; Rika Fira Zwagery; Bunga Azharah; Fatimah Azzahra (University of Muhammadiyah Malang, 2022)
Parenting patterns will determine how parents behave in preventing and overcoming stunting. Community service in the form of psychoeducation through online seminars (webinar) is considered necessary to provide understanding and knowledge to parents about stunting and the role of parents in child care to prevent and overcome stunting. Psychoeducation activities are carried out through webinars due to the Covid-19 pandemic conditions which make it impossible to gather in one place. This psychoeducation activity was attended by 88 participants consisting of housewives, working mothers and teenagers. The selection of participants was done by distributing activity posters and contacting several PAUDs. The effectiveness of psychoeducational activities is seen through an open questionnaire given to participants before and after the implementation of the activity. An open questionnaire in the form of questions that participants must answer descriptively to see the participants' responses to the implementation of psychoeducation. The results obtained from psychoeducational activities through this webinar showed that participants found this activity useful and provided new knowledge about stunting, especially parenting